2014
DOI: 10.1038/ki.2013.476
|View full text |Cite
|
Sign up to set email alerts
|

Personalized prophylactic anticoagulation decision analysis in patients with membranous nephropathy

Abstract: Primary membranous nephropathy is associated with increased risk of venous thromboembolic events, which are inversely correlated with serum albumin levels. To evaluate the potential benefit of prophylactic anticoagulation (venous thromboembolic events prevented) relative to the risk (major bleeds), we constructed a Markov decision model. The venous thromboembolic event risk according to serum albumin was obtained from an inception cohort of 898 patients with primary membranous nephropathy. Risk estimates of he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 31 publications
1
56
0
4
Order By: Relevance
“…Low serum albumin (<28 g/l) in multivariate analysis was the dominant factor associated with a higher incidence of VTE. Recently, a risk-benefit tool has been developed to help clinicians in their decision-making based on the data surrounding the question of prophylactic anticoagulation, which takes into account not only the risks of thromboembolism but also the risks of bleeding (www.gntools.com) [48]. Interestingly, episodes of VTE were not shown to affect renal survival.…”
Section: Conservative Therapymentioning
confidence: 99%
“…Low serum albumin (<28 g/l) in multivariate analysis was the dominant factor associated with a higher incidence of VTE. Recently, a risk-benefit tool has been developed to help clinicians in their decision-making based on the data surrounding the question of prophylactic anticoagulation, which takes into account not only the risks of thromboembolism but also the risks of bleeding (www.gntools.com) [48]. Interestingly, episodes of VTE were not shown to affect renal survival.…”
Section: Conservative Therapymentioning
confidence: 99%
“…The KDIGO guideline suggests that in patients with marked reductions in serum albumin (<25 g/L) and additional risks for thrombosis, prophylactic anticoagulant therapy might be considered [10]. Lee et al developed a useful tool to provide a more personalized decision about the initiation of prophylactic anticoagulation [18]. Recently, it became clear that the risk of arterial thrombosis is also high [19].…”
Section: Introductionmentioning
confidence: 99%
“…Although thrombosis could potentially be prevented with prophylactic anticoagulation, this approach remains controversial because of the treatment-associated risk of bleeding complications. [10][11][12] Recent epidemiologic studies have revealed that both proteinuria and serum albumin may be associated with the likelihood of thrombosis, with higher proteinuria and lower serum albumin correlating with increased thrombotic risk, suggesting that disease severity may be directly correlated with the severity of coagulation system derangement. [13][14][15][16][17][18] Thus, determining the relationship between hypercoagulopathy and these markers of disease severity may lead to the identification of clinically meaningful urine protein and/or serum albumin levels beyond which prophylaxis with anticoagulants may be warranted.…”
mentioning
confidence: 99%